A revision of the New World genus Penniverpa Irwin and Lyneborg (Diptera: Therevidae: Therevinae) - Webb, Donald W.; Metz, Mark A. (Zootaxa, 2008)
The genus Penniverpa Irwin and Lyneborg is revised and includes 13 species from the New World. Six of these: Penniverpa bradleyi Webb, n. sp., P. chersonesa Webb, n. sp., P. epidema Webb n. sp., P. evani Webb, n. sp., P. insular Webb, n. sp., P. megaplax Webb, n. sp., P. multisetosa Webb, n. sp., and P. unispinosa Webb, n. sp. are new to science. Penniverpa longipes (Loew) is placed in the genus Insulatitan (n. comb.) and becomes the senior synonym of Insulatitan romaynae Metz & Irwin, n. syn. and Psilocephala gracilis Kröber is placed in the genus Penniverpa (n. comb.) and is the senior synonym of Penniverpa brunnipennis (Kröber), n. syn. Penniverpa alvadusta Irwin & Webb is found to be a junior synonym of P. alvatra Irwin & Webb, n. syn. and Penniverpa lyneborgi Irwin & Webb and P. stigmaticalis (Schiner) are found to be junior synonyms of Penniverpa dives (Schiner), n. syn. Each species is described or redescribed with illustrations of their genitalia, a key to their identification, and a map of their distribution.